STUDIES ON SEROPREVALENCE OF BRUCELLOSIS AND IBR IN CATTLE IN JALPAIGURI DIS TRICT OF WEST BENGAL - MAITI, LAKSHMAN CHANDRA; CHOWDHIJRY, JAYANTA; BOSE, DEBADIN; BHATTACHARYA, MALAY; ROY, BIDYUT BARAN (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2009)
‘Brucellosis’ also known as Bang’s Disease or Contagious Abortion, is an acute or chronic infectious and contagious disease of domestic animals, that causes placentitis and abortion Whereas, Infectious Bovine Rhinotracheitis (IBR) which is also known as Infectious Pustular Vulvovaginítis(IPV) or Red Nose, is an acute contagious viral disease (Herpes virus) of cattle characterized by high rise of temperature, rhinitis, dyspnoea, meningoencephalitis, keratoconjunctivitis, pustular vulvovaginitis and abortion. Studies on seroprevalence of Bruce llosis and ¡BR in cattle in Jalpaiguri district (Doors region of West Bengal, India) revealed that ¡BR is more prevalent .(15.4%) than Brucellosis(1.l%).